Unveiling the therapeutic potential of berberine: its therapeutic role and molecular mechanisms in kidney diseases - Fan, Zhongyu; Wei, Xuejiao; Zhu, Xiaoyu; Yang, Kun; Tian, Ling; Wang, Xiaoyan; Du, Yujun; Yang, Liming (Frontiers in Pharmacology, 2025)
Berberine (BBR) is a pentacyclic benzylisoquinoline alkaloid widely distributed across various medicinal plants. Recent studies have demonstrated that berberine possesses a broad spectrum of pharmacological activities, including not only antioxidant properties but also the ability to lower blood glucose, modulate lipid profiles, and mitigate inflammation. These findings suggest that berberine holds significant potential as a therapeutic agent for renal diseases, highlighting its substantial research value. Moreover, when administered orally, berberine has been shown to exhibit a wide therapeutic safety margin. Several studies have identified berberine’s renoprotective effects across a range of kidney disorders, including diabetic nephropathy, renal fibrosis, renal aging, kidney toxicity induced by chemotherapy and antibiotics. These properties underscore berberine’s evolving therapeutic potential for both acute kidney injury (AKI) and chronic kidney disease (CKD). In summary, the research discussed in this article provides a comprehensive overview of the renoprotective effects of BBR and elucidates the molecular mechanisms underlying its therapeutic potential in the treatment of various renal disease. Furthermore, the article underscores the significance of berberine as a promising therapeutic agent for the treatment of kidney disorders.